The PV System Doctor – Comprehensive diagnosis of PV system installations. (September 2017) - Zhang, Yin; Sakhuja, Mridul; Lim, Fang Jeng; Tay, Stephen; Tan, Congyi; Bieri, Monika; Krishnamurthy, Vijay Anand; Wang, Darryl; Krishnakumar, Parvathy K.; Ha, James; Zhao, Lu; Reindl, Thomas
Abstract: Due to an increased adoption of photovoltaic (PV) systems globally, degradation and failure of PV installations in the field that lead to under-performing systems and eventually to lower financial returns have begun to attract more attention. This is even more pronounced in tropical climates where the operating conditions are harsher due to higher humidity and temperature levels compared to temperate climates. Hence, an understanding of the modes and mechanisms behind under-performing PV systems is critical in ensuring reliable and durable operation of PV assets. Commonly, a degraded or faulty module is isolated and taken off-site to a laboratory for inspection and testing. This procedure adds unnecessary transportation costs, and possible system downtime which may lead to additional revenue losses. Furthermore, these off-site diagnoses may not correctly represent the behavior of the PV module under real operating conditions. In this paper, we present an in-situ, non-destructive methodology ("PV System Doctor") for on-site diagnostic tests carried out on several PV systems in Singapore. The non-destructive tools utilised in this work are thermal imaging and a mobile daytime luminescence imaging system for both electroluminescence and photoluminescence. The analysis and findings from our diagnostic tests are presented. Our technique helps system owners quickly and accurately identify degraded or faulty PV modules without the need to remove them from the installation.